2023
DOI: 10.1111/dar.13622
|View full text |Cite
|
Sign up to set email alerts
|

Media reporting on alcohol and other drugs in Australia and the Mindframe guidelines: Baseline data

Abstract: Introduction:The aim of this study was to generate a baseline database of print media reporting on alcohol and other drug (AOD) issues prior to the release of the Mindframe guidelines in March 2019. Specifically, to: (i) describe the content associated with media entries that focus on AOD use in Australian news media;(ii) determine how the media entries compare to several domains associated with recently developed Mindframe guidelines for publicly reporting on AOD; and (iii) identify content factors associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Accompanying this increase in focus on the drug has been a rise in public concern, with methamphetamines ranked as the drug of most serious concern for the general community in the 2019 NDSHS [30]. A study examining media reporting on alcohol and other drugs in Australia identified that media entries on methamphetamine overwhelming focused on criminal justice, crime or law enforcement [31]. Comparatively, only one‐third of alcohol‐related media entries focused on crime/law issues.…”
Section: Discussionmentioning
confidence: 99%
“…Accompanying this increase in focus on the drug has been a rise in public concern, with methamphetamines ranked as the drug of most serious concern for the general community in the 2019 NDSHS [30]. A study examining media reporting on alcohol and other drugs in Australia identified that media entries on methamphetamine overwhelming focused on criminal justice, crime or law enforcement [31]. Comparatively, only one‐third of alcohol‐related media entries focused on crime/law issues.…”
Section: Discussionmentioning
confidence: 99%
“…The engineered prompt structure featured a role, task, requirements, and instructions and was developed based on GPT-4's internal prompts, university guides, and developer guides [24,25]. These prompts were also written to reflect best-practice communication guidelines in relation to mental health and substance use [26][27][28]. For each of the 4 factsheets, 3 prompts were applied in 3 steps within the same chat (Textbox 2), and a new chat was opened for each topic.…”
Section: Evidence-based Factsheetsmentioning
confidence: 99%
“…Media guidelines for safe, respectful, and responsible communication about mental health and substance use are important to inform the development of nonstigmatizing health materials. Best-practice public communication guidelines for mental health and substance use were used to evaluate GPT-4-generated responses and consumer materials [26][27][28].…”
Section: Communication Guidelinesmentioning
confidence: 99%
See 1 more Smart Citation